The performance of stock portfolios: Evidence from analysing Malaysia case, and implication for open innovation - Ariful Hoque; Sharmeen Rakhi; Kamrul Hassan; Thi Le (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This research examines the performance of the Islamic stock portfolio (ISP) and conventional stock portfolio (CSP) for the five industrial sectors and market in Malaysia. The capital asset pricing model statistics indicate that the ISP provides a higher return with a lower systematic risk compared to the CSP in different sectors; however, the ISP and CSP perform equally in the market. The non-parametric stochastic dominance approach reveals that the ISP is better than the CSP for portfolio return without considering the riskiness for all sectors except properties; further, the ISP outperforms the CSP under the market condition. Economic significance analysis identifies that the expected financial loss of the ISP is lower than that of the CSP in all sectors other than properties; the anticipated financial loss of the ISP is significantly less than that of the CSP in the market situation. The overall findings imply that the risk-sharing ISP is superior to the risk-bearing CSP for better returns at the sector as well as the market level.
Keywords: 650; historical VaR; Islamic portfolio; stochastic dominance